BIRTH OF A VOLCANIC PASSIVE MARGIN IN CAMBRIAN TIME: RIFT PALEOGEOGRAPHY OF THE OSSA-MORENA ZONE, SW SPAIN - Etxebarria M.; Apraiz A.; Eguíluz L.; Chalot-Prat F. (My University, 2006)
Mapping at 1:10000 scale of both north (N) and south (S) flanks of the Variscan Monesterio antiform in the Ossa-Morena Zone (southern Spain), in association with detailed petrographic and major element analyses of magmatic rocks has revealed the building of a passive, but volcanically active, oceanic margin in Cambrian time. This margin was located in northern Gondwana and represents the beginning of an extensional tectonic regime that concluded with the opening of the Rheic Ocean. At time of eruption (Middle Cambrian), the N flank was located on the northern coastline of a marine basin in the process of passive rifting. The vents, mainly located in its western part, were subaerial continental and/or shallow marine. On the S flank, eruptions and deposits were shallow marine, occurring as lava flows and pillows interstratified within shallow marine sediments. On both flanks, intrusives were emplaced after the extrusives. Lateral thickness variations of the sedimentary deposits testify to the building, during four distinct periods, of a rifted passive margin with a shifting locus of volcanic activity over time. The composition of magmas was bimodal. The mafic magmas are silica-saturated, alkaline to sub-alkaline and somewhat Ti-rich, perhaps originating from partial melting of a subcontinental mantle that was less metasomatized with time. The youngest magmatism, with an affinity close to that of MORB, likely had an asthenospheric source. The alkaline felsic products are diverse and may have originated from a very heterogeneous continental crust. In each set, partial melting relationships prevail
Keywords: Cambrian; Paleozoic::Cambrian; Палеозой::Кембрийская